2020
DOI: 10.1002/adfm.202007026
|View full text |Cite
|
Sign up to set email alerts
|

Zwitterionic AIEgens: Rational Molecular Design for NIR‐II Fluorescence Imaging‐Guided Synergistic Phototherapy

Abstract: Supporting information for this article is given via a link at the end of the document.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 108 publications
(104 citation statements)
references
References 50 publications
(23 reference statements)
0
101
0
Order By: Relevance
“…Previous studies have demonstrated two design principles for NIR‐activated AIE: 1) integration of strong electron donor (D) and acceptor (A) units into the conjugated system and 2) the prolongation of the effective conjugated length between these units. [ 66,73,74 ] The strong D–A pair in AIE molecules enables efficient electron transfer under low‐energy excitation, thus leading to reduced electronic bandgaps and bathochromic absorption/emission. The long conjugation normally results in low bandgap energy.…”
Section: Physical Properties Of Aie Nanoprobesmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies have demonstrated two design principles for NIR‐activated AIE: 1) integration of strong electron donor (D) and acceptor (A) units into the conjugated system and 2) the prolongation of the effective conjugated length between these units. [ 66,73,74 ] The strong D–A pair in AIE molecules enables efficient electron transfer under low‐energy excitation, thus leading to reduced electronic bandgaps and bathochromic absorption/emission. The long conjugation normally results in low bandgap energy.…”
Section: Physical Properties Of Aie Nanoprobesmentioning
confidence: 99%
“…In recent attempts, NIR‐II‐emitting AIE nanoprobes have been used to determine the therapeutic time interval (the optimal time for conducting therapy after drug intake) for efficient cancer therapy. Wang's group [ 66,73,74 ] prepared and used three types of AIE nanoprobes for multimodal therapy. According to the NIR‐II fluorescence images, the optimal therapeutic window was found to be between 1 and 12 h post injection.…”
Section: Fluorescence Imaging Of Aie Nanoprobesmentioning
confidence: 99%
See 2 more Smart Citations
“…[15][16][17][18][19][20][21] Combining FRI and photototherapy in one molecule for tumor theranostics is reasonable based on the ingenious design and supramolecular assembly. [22][23][24][25][26] Compared with the traditional cancer therapies, photothermal therapy (PTT) or photodynamic therapy has many advantages, such as the low invasiveness, minimal side effects, and high specificity. [27][28][29][30][31][32][33][34][35] Although great progresses have been made in various PTT systems, there is little attention to synthesize photothermal agents (PTAs) with small sizes for optimal therapeutic effects.…”
mentioning
confidence: 99%